ANALISA LAJU PERPINDAHAN PANAS PADA KOLEKTOR SURYA TIPE PELAT DATAR DENGAN ABSORBER PASIR - Wirawan, Made; Sutanto, Rudy (Universitas Mataram, 2011)
Solar energy constitute one of potential alternative energy to develop as a back up of energy. Especially for countries in khatulistiwa location belonging to Indonesia. For use solar energy needful collector that using absorber. Using sand as a absorber make up step for increase value and profit of sand, in a economics manner the price more cheap and easy to obtain than another absorber. The analysis use sand as a alternative absorber for solar collector did for understand rate of heat transfer to acceptanceof water. Dimention of collector are 560 mm x 310 mm with thick of sand absorber 10 mm and 1.2 mm for aluminum plate as a comparator. Observation did begin 10.00 am until 14.00 pm for the two of them in the weather clear sky. The rate of water in this research are 200 cc/min, 250 cc/min and 300 cc/mn for another dan at the same time. The result of analysis be obtained heat absortion by water for solar collector with aluminum absorber more large than sand absorber. The debit of water more and more large in the collector so absorb heat by water more large because incretion the mass flow rate of water (m  ). The heat losses in the solar collector aluminum absorber more than sand absorber.